2005
DOI: 10.1051/rnd:2005014
|View full text |Cite
|
Sign up to set email alerts
|

Contributing factors and variability of energy expenditure in non-obese, obese, and post-obese adolescents

Abstract: -Energy expenditure (EE) is a major determinant of energy balance and body composition. The objectives of this paper were to review the contributing factors of the main components of daily EE (DEE) and the inter-individual variability in these components in non-obese (NOb), obese (Ob), and post-obese (POb) adolescents. Body composition especially fat-free mass (FFM), is the major determinant of the basal metabolic rate which contributes 50-70% of DEE, whereas fat mass (FM) is a significant factor only in obese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 71 publications
0
20
0
2
Order By: Relevance
“…Organs such as the liver, brain, heart and kidney collectively consume about 60% of an endotherm's total energy expenditure and consequently are major contributors to overall RMR (Daan et al, 1990;Vermorel et al, 2005). The elevation in RMR of the cold group was presumably related to metabolic and/or morphological adjustments, including changes in organ mass, required to meet the energy demands of acclimation to colder temperature conditions.…”
Section: Effects Of Temperature and Photoperiod On Morphology And Phymentioning
confidence: 99%
“…Organs such as the liver, brain, heart and kidney collectively consume about 60% of an endotherm's total energy expenditure and consequently are major contributors to overall RMR (Daan et al, 1990;Vermorel et al, 2005). The elevation in RMR of the cold group was presumably related to metabolic and/or morphological adjustments, including changes in organ mass, required to meet the energy demands of acclimation to colder temperature conditions.…”
Section: Effects Of Temperature and Photoperiod On Morphology And Phymentioning
confidence: 99%
“…We found that sizeindependent comparisons could be made using FFM. Moreover, previous studies succeeded in comparing physical activity using EE/FFM even between obese and nonobese adult subjects (Meijer et al, 1992) and between children and adolescents (Ekelund et al, 2004;Vermorel et al, 2005). On the basis of these results it appears that FFM has characteristics of both BW and RMRs.…”
Section: Discussionmentioning
confidence: 81%
“…However, differences in the relationships between body size and L-RMR and S-RMR were not clarified sufficiently. There is an alternative way to adjust EE for body size, namely, EE/FFM, with previous studies in children and adolescents suggesting that FFM may be the most appropriate variable for normalization of EE during physical activities (Ekelund et al, 2004;Vermorel et al, 2005). Intensity of daily total activity can be estimated by dividing total energy expenditure (TEE) by BW (TEE/BW) or by RMRs (TEE/L-RMR and TEE/S-RMR).…”
Section: ) Department Of Food and Nutritional Sciences Graduate Schmentioning
confidence: 99%
“…Pour qu'un adolescent dépasse au cours d'une activité le seuil de deux fois la dépense d'énergie au cours du sommeil, il est nécessaire que cette activité se déroule à l'extérieur. La simple marche en est la première occasion [5]. Toutefois, chez les adolescents, les activités spontanées mais suffisamment vigoureuses semblent conférer la meilleure protection contre l'obésité [6].…”
Section: Diminution De L'activité Physique Et Augmentation Des Comporunclassified